A high hydrothermal stability molecular sieve composite catalyst, a preparation method and application thereof

CN122352337BActive Publication Date: 2026-10-16LIUPANSHUI NORMAL UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610689798.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-05-19
Publication Date
2026-10-16
Estimated Expiration
2046-05-19

AI Technical Summary

Technical Problem

然而,该类碳包覆结构在长时间高温水蒸气气氛下仍会发生缓慢气化反应(C+H2O→CO+H2),导致碳层逐步失去保护作用,难以长期稳定地保护内部二氧化硅载体;同时,石墨化碳包覆的多孔二氧化硅在高温含氧环境下也难以维持原有结构稳定性,从而限制了其在实际反应条件下的应用

Benefits of technology

本发明通过构建羟基磷灰石(HAP)改性二氧化硅分子筛的复合载体结构,利用羟基磷灰石的耐水热特性与分子筛的限域效应协同作用,显著提升催化剂的综合性能。具体而言:羟基磷灰石包覆层通过强表面载体相互作用(如Ca-O-P键)锚定活性金属组分,有效抑制水分子对二氧化硅分子筛骨架的侵蚀,避免传统催化剂在高温高湿条件下因Si-OH基团缩合导致的结构坍塌;分子筛的微孔/介孔结构精准调控活性金属的分散度,结合HAP包覆层提供的化学限域作用,显著降低金属颗粒迁移与烧结倾向。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122352337B_ABST
    Figure CN122352337B_ABST
Patent Text Reader

Abstract

The application discloses a high hydrothermal stability molecular sieve composite catalyst and a preparation method and application thereof, and belongs to the technical field of catalyst preparation. In the application, a Ca source is introduced into a molecular sieve channel in advance for fixation, and then a step-by-step hydrothermal synthesis and low-temperature calcination process is adopted, so that interface lattice matching of a HAP coating layer and the molecular sieve is realized, and structure instability caused by lattice mismatching is avoided. The high hydrothermal stability molecular sieve composite catalyst exhibits excellent hydrothermal stability and reaction activity in catalytic combustion of methane and hydrogen production by reforming, the preparation process condition is controllable, the step is simple, the application is suitable for industrialized continuous production, and an innovative solution is provided for development of a long-service-life catalyst under a high-temperature and high-humidity environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of catalyst preparation technology, specifically relating to a high hydrothermal stability molecular sieve composite catalyst, its preparation method, and its application. Background Technology

[0002] Catalytic combustion and reforming of methane for hydrogen production is an important technological pathway for the efficient conversion and utilization of natural gas. It is of great significance in reducing carbon emissions, producing clean hydrogen energy, and meeting the application needs of fuel cells and distributed energy supply. These reactions are typically carried out at high temperatures of 600–1000°C, and the reaction system often involves high-pressure water vapor. Therefore, high requirements are placed on the structural stability, activity retention, and service life of the catalyst under high-temperature hydrothermal conditions.

[0003] In existing catalyst systems, molecular sieve materials have attracted widespread attention in thermocatalytic reactions such as methane catalytic combustion and reforming for hydrogen production due to their regular pore structure, high specific surface area, and excellent pore confinement effect, which effectively suppress the migration and sintering of active metal particles. However, the molecular sieve framework is usually mainly composed of Si-O-Si bonds. Under high temperature and high water vapor partial pressure conditions, water vapor slowly hydrolyzes its framework structure, leading to the formation of framework defects, which further induces framework rearrangement, local amorphization, and even pore collapse. Ultimately, this weakens the confinement and stabilization effect of the molecular sieve on the active components, causing the active components to agglomerate and sinter, thereby leading to a decrease in catalytic activity and catalyst deactivation. Therefore, developing composite molecular sieve catalysts that can maintain structural stability and catalytic performance under high temperature and hydrothermal conditions has significant research value and practical application significance.

[0004] To address the aforementioned issues, existing technologies have explored ways to improve catalyst performance through composite support design. For example, some studies have employed graphitized carbon to coat mesoporous silica, aiming to balance pore confinement with water resistance. However, this type of carbon-coated structure still undergoes a slow vaporization reaction (C + H₂O → CO + H₂) under prolonged high-temperature steam atmospheres, causing the carbon layer to gradually lose its protective function and making it difficult to stably protect the internal silica support in the long term. Furthermore, the porous silica coated with graphitized carbon struggles to maintain its structural stability under high-temperature, oxygen-containing environments, thus limiting its application under practical reaction conditions.

[0005] Therefore, the existing technology lacks a composite catalyst that can simultaneously take into account the molecular sieve channel confinement effect, support structure stability, and the anti-sintering ability of the active component under high temperature hydrothermal conditions. Summary of the Invention

[0006] The purpose of this invention is to provide a high hydrothermal stability molecular sieve composite catalyst, its preparation method, and its applications. The provided high hydrothermal stability molecular sieve composite catalyst should exhibit good activity and stability in methane catalytic combustion and methane reforming for hydrogen production, and its preparation conditions should be simple, reproducible, and easily industrialized.

[0007] To achieve the above objectives, the present invention provides the following technical solution: One of the technical solutions of this invention is to provide a method for preparing a high hydrothermal stability molecular sieve composite catalyst, comprising the following steps: A template agent and a calcium source are dissolved in water, and the pH value is adjusted according to the choice of template agent. Then, a silicon source is added, and hydrothermal crystallization is performed once. The solid is separated and dried to obtain a Ca-doped molecular sieve precursor. The Ca-doped molecular sieve precursor is dispersed in water, and the pH value is adjusted to 11-12. A phosphate solution with a pH value of 11-12 is added until the Ca / P atomic ratio of the system is 1.60-1.67. After stirring, a second hydrothermal crystallization is performed, and the solid is separated and dried. Then, it is calcined once to obtain a hydroxyapatite-modified molecular sieve. The hydroxyapatite-modified molecular sieve is mixed with a solution containing an active metal precursor, and stirred so that the hydroxyapatite-modified molecular sieve completely absorbs the solution containing the active metal precursor. Then, it is dried and calcined a second time to obtain the high hydrothermal stability molecular sieve composite catalyst. The active metal in the active metal precursor includes nickel or palladium.

[0008] Preferably, the template agent includes Prönnicke P123, Prönnicke F127, or tetrapropylammonium hydroxide (TPAOH).

[0009] More preferably, when the template agent is Pluronic P123 or Pluronic F127, the pH value is adjusted to 1-2 before adding the silicon source; when the template agent is tetrapropylammonium hydroxide, the pH value is adjusted to 10-12 before adding the silicon source.

[0010] Optionally, the calcium source includes calcium chloride.

[0011] Optionally, the silicon source includes tetraethyl orthosilicate.

[0012] Preferably, the molar ratio of Ca in the calcium source to Si in the silicon source is (0.5~2):10.

[0013] Preferably, the active metal in the active metal precursor accounts for 0.5-3% of the mass of the hydroxyapatite-modified molecular sieve.

[0014] Preferably, the temperature of the first hydrothermal crystallization is 100~200℃ and the time is 24~72h.

[0015] Optionally, the phosphate includes ammonium hydrogen phosphate.

[0016] Preferably, the stirring time before secondary hydrothermal crystallization is 12-24 hours, and more preferably, it is sealed stirring.

[0017] Preferably, the temperature of the secondary hydrothermal crystallization is 80~100℃, and the time is 5~24h.

[0018] Preferably, the temperature of the first calcination is 500~600℃, the holding time is 4~8h, and the heating rate is 5~10℃ / min.

[0019] Preferably, the stirring time after mixing the hydroxyapatite-modified molecular sieve with the solution containing the active metal precursor is 6-12 hours, and more preferably, it is sealed stirring.

[0020] Preferably, the secondary calcination temperature is 400~600℃, the holding time is 3~6h, and the heating rate is 5℃ / min.

[0021] Alternatively, the active metal precursor may include nickel acetate or palladium acetate.

[0022] Preferably, when the template agent and the calcium source are dissolved in water, an auxiliary metal precursor is also added, wherein the auxiliary metal in the auxiliary metal precursor includes cerium or lanthanum.

[0023] The Ce-OP and La-OP bonds formed by the auxiliary metal elements can anchor the active metal components, effectively inhibiting the erosion of the silica molecular sieve framework by water molecules and avoiding the structural collapse of traditional catalysts caused by the condensation of Si-OH groups under high temperature and high humidity conditions. The redox properties of the auxiliary metal elements can further enhance the electronic interaction between the metal and the support, and promote the adsorption and activation of reactant molecules at the active sites.

[0024] Optionally, the auxiliary metal precursor includes cerium nitrate or lanthanum nitrate.

[0025] More preferably, the molar ratio of the auxiliary metal in the auxiliary metal precursor to Ca in the calcium source is (0~3):10, and is not 0.

[0026] The second technical solution of the present invention provides a high hydrothermal stability molecular sieve composite catalyst prepared according to the above-mentioned preparation method of high hydrothermal stability molecular sieve composite catalyst.

[0027] The third technical solution of the present invention provides an application of the above-mentioned high hydrothermal stability molecular sieve composite catalyst in catalytic methane reforming for hydrogen production or catalytic combustion of methane.

[0028] The beneficial technical effects of the present invention are as follows: This invention constructs a composite support structure for hydroxyapatite (HAP)-modified silica molecular sieves, leveraging the synergistic effect of hydroxyapatite's hydrothermal resistance and the molecular sieve's confinement effect to significantly enhance the overall performance of the catalyst. Specifically, the hydroxyapatite coating anchors the active metal component through strong surface-support interactions (such as Ca-OP bonds), effectively inhibiting the erosion of the silica molecular sieve framework by water molecules and preventing structural collapse caused by Si-OH group condensation under high temperature and humidity conditions, as is common in traditional catalysts. The microporous / mesoporous structure of the molecular sieve precisely regulates the dispersion of the active metal, and combined with the chemical confinement effect provided by the HAP coating, significantly reduces metal particle migration and sintering tendency.

[0029] This invention first introduces a Ca source into the molecular sieve channels for fixation, and then employs a stepwise hydrothermal synthesis and low-temperature calcination process to achieve interfacial lattice matching between the HAP coating layer and the molecular sieve, avoiding structural instability caused by lattice mismatch. This molecular sieve composite catalyst exhibits excellent hydrothermal stability and reactivity in methane catalytic combustion and reforming for hydrogen production. Its preparation process is controllable and simple, suitable for continuous industrial production, and provides an innovative solution for the development of long-life catalysts under high-temperature and high-humidity conditions. Attached Figure Description

[0030] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0031] Figure 1 The images show the characterization of the catalyst prepared in Example 1 before and after the catalytic steam reforming reaction of methane; where (a) to (c) are TEM bright-field images of the catalyst at different magnifications before the reaction, (d) is a TEM dark-field image of the catalyst before the reaction, (e) to (i) are EDS mapping images of Si, O, Ca, P and Ni of the catalyst before the reaction, (j) to (l) are TEM bright-field images of the catalyst at different magnifications after the reaction, (m) is a TEM dark-field image of the catalyst after the reaction, and (n) to (r) are EDS mapping images of Si, O, Ca, P and Ni of the catalyst after the reaction.

[0032] Figure 2 The images show the characterization of the catalyst prepared in Example 4 before and after catalyzing the steam reforming of methane; where (a) and (b) are SEM images of the catalyst before the reaction at different magnifications, (c) is the SEM image of the catalyst after the reaction, and (d) to (i) are EDS mapping images of Si, O, P, Ce, Ni and Ca elements, respectively.

[0033] Figure 3 The images show the characterization of the catalyst prepared in Comparative Example 3 before and after catalyzing the steam reforming of methane; where (a) and (b) are SEM images of the catalyst before the reaction at different magnifications, (c) is the SEM image of the catalyst after the reaction, and (d) to (g) are EDS mapping images of Si, O, Ce and Ni elements, respectively.

[0034] Figure 4 The images show the characterization of the catalyst prepared in Comparative Example 5 before and after catalyzing the steam reforming of methane; where (a) is a TEM dark field image of the catalyst before the reaction, (b) is an EDS mapping image of the Ni element of the catalyst before the reaction, (c) is a TEM dark field image of the catalyst after the reaction, and (d) is an EDS mapping image of the Ni element of the catalyst after the reaction.

[0035] Figure 5 The results show the stability test results of the catalysts prepared in Examples 1, 3, 4 and Comparative Examples 1, 3, 5 in the catalytic steam reforming reaction of methane.

[0036] Figure 6 The results show the stability test results of the catalysts prepared in Examples 2 and 5 and Comparative Examples 2 and 4 in the catalytic combustion reaction of methane. Detailed Implementation

[0037] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention. It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the present invention.

[0038] It should be noted that any aspects not described in detail in this invention are conventional practices in the field and are not the focus of this invention.

[0039] Furthermore, regarding the numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Any stated value or intermediate value within a stated range, as well as each smaller range between any other stated value or intermediate value within said range, are also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.

[0040] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar to or equivalent to those described herein may be used in the implementation or testing of this invention.

[0041] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.

[0042] Unless otherwise specified, "room temperature" in this invention refers to 15~30℃; and "normal pressure" unless otherwise specified refers to 0.1MPa.

[0043] All raw materials used in this invention were purchased from the market.

[0044] Example 1 In this embodiment, the molar ratio of Ca to Si in the catalyst is 1:10, the template agent is TPAOH, no auxiliary metal precursor salt is added, and the active metal precursor salt is nickel acetate. The nickel loading on the catalyst support in nickel acetate is 2wt%. The specific preparation steps are as follows: 1) Preparation of Ca-doped molecular sieve precursor: At room temperature, 14.2 mL of TPAOH (25 wt% aqueous solution) and 2000 mg of calcium chloride were dissolved in 17 mL of deionized water, the pH of the solution was adjusted to 11, and then 10 mL of tetraethyl orthosilicate was added and mixed evenly. The solution was placed in a sealed reaction vessel and hydrothermally crystallized at 170 °C for 72 h. After filtration, it was dried in an oven at 80 °C to obtain the Ca-doped molecular sieve precursor. 2) Preparation of hydroxyapatite-modified molecular sieve composite support: The Ca-doped molecular sieve precursor obtained in step 1) was added to 20 mL of deionized water and stirred continuously at room temperature. The pH was adjusted to 11, and then ammonium hydrogen phosphate ((NH4)2HPO4) solution with pH 11 was added until the Ca / P atomic ratio in the system was 1.67. The mixture was sealed and stirred for 12 h. The solution was then hydrothermally crystallized at 90 °C for 12 h, filtered, dried, and finally calcined in a muffle furnace at 600 °C for 4 h at a heating rate of 5 °C / min to obtain the hydroxyapatite-modified molecular sieve composite support. 3) Loading of active metal components: At room temperature, 34.6 mg of nickel acetate (Ni(CH3COO)2·4H2O) was weighed and dissolved in 20 mL of ethanol. 0.4 g of the composite support obtained in step 2) was added, sealed and stirred for 12 h, dried, and calcined in a muffle furnace at 600 °C for 4 h at a heating rate of 5 °C / min to obtain the final catalyst.

[0045] Example 2 In this embodiment, the molar ratio of Ca to Si in the catalyst is 1:10, the template agent is TPAOH, no auxiliary metal precursor salt is added, and the active metal precursor salt is palladium acetate. The loading of palladium on the catalyst support is 1 wt%. The specific preparation steps are as follows: 1) Preparation of Ca-doped molecular sieve precursor: At room temperature, 14.2 mL of TPAOH (25 wt% aqueous solution) and 2000 mg of calcium chloride were dissolved in 17 mL of deionized water, the pH of the solution was adjusted to 11, and then 10 mL of tetraethyl orthosilicate was added and mixed evenly. The solution was placed in a sealed reaction vessel and hydrothermally crystallized at 170 °C for 72 h. After filtration, it was dried in an oven at 80 °C to obtain the Ca-doped molecular sieve precursor. 2) Preparation of hydroxyapatite-modified molecular sieve composite support: The Ca-doped molecular sieve precursor obtained in step 1) was added to 20 mL of deionized water and stirred continuously at room temperature. The pH was adjusted to 11, and then ammonium hydrogen phosphate ((NH4)2HPO4) solution with pH 11 was added until the Ca / P atomic ratio in the system was 1.67. The mixture was sealed and stirred for 12 h. The solution was then hydrothermally crystallized at 90 °C for 12 h, filtered, dried, and finally calcined in a muffle furnace at 600 °C for 4 h at a heating rate of 5 °C / min to obtain the hydroxyapatite-modified molecular sieve composite support. 3) Loading of active metal components: At room temperature, 8.5 mg of palladium acetate (Pd(CH3COO)2) was weighed and dissolved in 20 mL of ethanol. 0.4 g of the composite support obtained in step 2) was added, sealed and stirred for 12 h, dried, and calcined in a muffle furnace at 400 °C for 4 h at a heating rate of 5 °C / min to obtain the final catalyst.

[0046] Example 3 In this embodiment, the molar ratio of Ca to Si in the catalyst is 2:10, the template agent is Prönnicke P123, no auxiliary metal precursor salt is added, and the active metal precursor salt is nickel acetate. The nickel loading on the catalyst support in nickel acetate is 2wt%. The specific preparation steps are as follows: 1) Preparation of Ca-doped molecular sieve precursor: At room temperature, 4g of Prönnicke P123 and 503mg of calcium chloride were dissolved in deionized water, the pH of the solution was adjusted to 1, and then 9mL of tetraethyl orthosilicate was added and mixed evenly. The solution was placed in a sealed reaction vessel and hydrothermally crystallized at 100℃ for 24h. After filtration, it was dried in an oven at 80℃ to obtain the Ca-doped molecular sieve precursor. 2) Preparation of hydroxyapatite-modified molecular sieve composite support: The Ca-doped molecular sieve precursor obtained in step 1) was added to 20 mL of deionized water and stirred continuously at room temperature. The pH was adjusted to 11, and then ammonium hydrogen phosphate ((NH4)2HPO4) solution with pH 11 was added until the Ca / P atomic ratio in the system was 1.67. The mixture was sealed and stirred for 12 h. The solution was then hydrothermally crystallized at 90 °C for 12 h, filtered, dried, and finally calcined in a muffle furnace at 600 °C for 4 h at a heating rate of 5 °C / min to obtain the hydroxyapatite-modified molecular sieve composite support. 3) Loading of active metal components: At room temperature, 34.6 mg of nickel acetate (Ni(CH3COO)2·4H2O) was weighed and dissolved in 20 mL of ethanol. 0.4 g of the composite support obtained in step 2) was added, sealed and stirred for 12 h, dried, and calcined in a muffle furnace at 600 °C for 4 h at a heating rate of 5 °C / min to obtain the final catalyst.

[0047] Example 4 In this embodiment, the molar ratio of Ca to Si in the catalyst is 2:10, the template agent is Prönnicke P123, the added auxiliary metal precursor salt is cerium nitrate, the molar ratio of Ce to Ca is 2.4:10, the active metal precursor salt is nickel acetate, and the nickel loading on the catalyst support is 2 wt%. The specific preparation steps are as follows: 1) Preparation of Ca-doped molecular sieve precursor: At room temperature, 4g of Prönnicke P123 and 503mg of calcium chloride were dissolved in deionized water, the pH of the solution was adjusted to 1, and then 9mL of tetraethyl orthosilicate was added and mixed evenly. The solution was placed in a sealed reaction vessel and hydrothermally crystallized at 100℃ for 24h. After filtration, it was dried in an oven at 80℃ to obtain the Ca-doped molecular sieve precursor. 2) Preparation of hydroxyapatite-modified molecular sieve composite support: 470.3 mg of cerium nitrate (Ce(NO3)3·6H2O) was dissolved in 20 mL of deionized water. The Ca-doped molecular sieve precursor obtained in step 1) was added to the solution and stirred continuously at room temperature. The pH was adjusted to 11, and then ammonium hydrogen phosphate ((NH4)2HPO4) solution with pH 11 was added until the Ca / P atomic ratio in the system was 1.67. The solution was sealed and stirred for 12 h. The solution was then hydrothermally crystallized at 90 °C for 12 h, filtered, dried, and finally calcined in a muffle furnace at 600 °C for 4 h at a heating rate of 5 °C / min to obtain the Ce-doped hydroxyapatite-modified molecular sieve composite support. 3) Loading of active metal components: At room temperature, 34.6 mg of nickel acetate (Ni(CH3COO)2·4H2O) was weighed and dissolved in 20 mL of ethanol. 0.4 g of the composite support obtained in step 2) was added, sealed and stirred for 12 h, dried, and calcined in a muffle furnace at 600 °C for 4 h at a heating rate of 5 °C / min to obtain the final catalyst.

[0048] Example 5 In this embodiment, the molar ratio of Ca to Si in the catalyst is 2:10, the template agent is Prönnicke P123, the added auxiliary metal precursor salt is lanthanum nitrate, the molar ratio of La to Ca is 2.4:10, the active metal precursor salt is palladium acetate, and the palladium loading on the catalyst support is 1 wt%. The specific preparation steps are as follows: 1) Preparation of Ca-doped molecular sieve precursor: At room temperature, 4g of Prönnicke P123 and 503mg of calcium chloride were dissolved in deionized water, the pH of the solution was adjusted to 1, and then 9mL of tetraethyl orthosilicate was added and mixed evenly. The solution was placed in a sealed reaction vessel and hydrothermally crystallized at 100℃ for 24h. After filtration, it was dried in an oven at 80℃ to obtain the Ca-doped molecular sieve precursor. 2) Preparation of hydroxyapatite-modified molecular sieve composite support: 470.9 mg of lanthanum nitrate (La(NO3)3·6H2O) was dissolved in 20 mL of deionized water. The Ca-doped molecular sieve precursor obtained in step 1) was added to the solution and stirred continuously at room temperature. The pH was adjusted to 11, and then ammonium hydrogen phosphate ((NH4)2HPO4) solution with pH 11 was added until the Ca / P atomic ratio in the system was 1.67. The solution was sealed and stirred for 12 h. The solution was then hydrothermally crystallized at 90 °C for 12 h, filtered, dried, and finally calcined in a muffle furnace at 600 °C for 4 h at a heating rate of 5 °C / min to obtain the Ce-doped hydroxyapatite-modified molecular sieve composite support. 3) Loading of active metal components: At room temperature, 8.5 mg of palladium acetate (Pd(CH3COO)2) was weighed and dissolved in 20 mL of ethanol. 0.4 g of the composite support obtained in step 2) was added, sealed and stirred for 12 h, dried, and calcined in a muffle furnace at 400 °C for 4 h at a heating rate of 5 °C / min to obtain the final catalyst.

[0049] Comparative Example 1 Same as Example 1, except that calcium chloride and ammonium hydrogen phosphate are not added, that is, the molecular sieve is not modified with hydroxyapatite. The specific preparation steps are as follows: 1) Preparation of molecular sieve precursor: At room temperature, 14.2 mL of TPAOH (25 wt% aqueous solution) was dissolved in 17 mL of deionized water, the pH of the solution was adjusted to 11, then 10 mL of tetraethyl orthosilicate was added and mixed evenly. The solution was placed in a sealed reaction vessel and hydrothermally crystallized at 170 °C for 72 h. After filtration, it was dried in an oven at 80 °C to obtain the molecular sieve precursor. 2) Preparation of molecular sieve support: The molecular sieve precursor obtained in step 1) was calcined in a muffle furnace at 600℃ for 4h with a heating rate of 5℃ / min to obtain the molecular sieve support. 3) Loading of active metal components: At room temperature, 34.6 mg of nickel acetate (Ni(CH3COO)2·4H2O) was weighed and dissolved in 20 mL of ethanol. 0.4 g of the molecular sieve support obtained in step 2) was added, sealed and stirred for 12 h, dried, and calcined in a muffle furnace at 600 °C for 4 h at a heating rate of 5 °C / min to obtain the final catalyst.

[0050] Comparative Example 2 Same as Example 2, except that calcium chloride and ammonium hydrogen phosphate are not added, that is, the molecular sieve is not modified with hydroxyapatite. The specific preparation steps are as follows: 1) Preparation of molecular sieve precursor: At room temperature, 14.2 mL of TPAOH (25 wt% aqueous solution) was dissolved in 17 mL of deionized water, the pH of the solution was adjusted to 11, then 10 mL of tetraethyl orthosilicate was added and mixed evenly. The solution was placed in a sealed reaction vessel and hydrothermally crystallized at 170 °C for 72 h. After filtration, it was dried in an oven at 80 °C to obtain the molecular sieve precursor. 2) Preparation of molecular sieve support: The molecular sieve precursor obtained in step 1) was calcined in a muffle furnace at 600℃ for 4h with a heating rate of 5℃ / min to obtain the molecular sieve support. 3) Loading of active metal components: At room temperature, 8.5 mg of palladium acetate (Pd(CH3COO)2) was weighed and dissolved in 20 mL of ethanol. 0.4 g of the composite support obtained in step 2) was added, sealed and stirred for 12 h, dried, and calcined in a muffle furnace at 400 °C for 4 h at a heating rate of 5 °C / min to obtain the final catalyst.

[0051] Comparative Example 3 Same as Example 4, except that calcium chloride and ammonium hydrogen phosphate are not added, that is, the molecular sieve is not modified with hydroxyapatite. The specific preparation steps are as follows: 1) Preparation of molecular sieve precursor: At room temperature, 4g of Prönnicke P123 was dissolved in deionized water, the pH of the solution was adjusted to 1, and then 9mL of tetraethyl orthosilicate was added and mixed evenly. The solution was placed in a sealed reaction vessel and hydrothermally crystallized at 100℃ for 24h. After filtration, it was dried in an oven at 80℃ to obtain the molecular sieve precursor. 2) Preparation of the additive metal-modified molecular sieve composite carrier: 470.3 mg of cerium nitrate (Ce(NO3)3·6H2O) was dissolved in 20 mL of deionized water. The molecular sieve precursor obtained in step 1) was added to the solution. The mixture was stirred continuously at room temperature, the pH was adjusted to 11, and the mixture was stirred in a sealed container for 12 h. The solution was then hydrothermally crystallized at 90 °C for 12 h, filtered, dried, and finally calcined in a muffle furnace at 600 °C for 4 h at a heating rate of 5 °C / min to obtain the Ce-modified molecular sieve composite carrier. 3) Loading of active metal components: At room temperature, 34.6 mg of nickel acetate (Ni(CH3COO)2·4H2O) was weighed and dissolved in 20 mL of ethanol. 0.4 g of the composite support obtained in step 2) was added, sealed and stirred for 12 h, dried, and calcined in a muffle furnace at 600 °C for 4 h at a heating rate of 5 °C / min to obtain the final catalyst.

[0052] Comparative Example 4 Same as Example 5, except that calcium chloride and ammonium hydrogen phosphate are not added, that is, the molecular sieve is not modified with hydroxyapatite. The specific preparation steps are as follows: 1) Preparation of molecular sieve precursor: At room temperature, 4g of Prönnicke P123 was dissolved in deionized water, the pH of the solution was adjusted to 1, and then 9mL of tetraethyl orthosilicate was added and mixed evenly. The solution was placed in a sealed reaction vessel and hydrothermally crystallized at 100℃ for 24h. After filtration, it was dried in an oven at 80℃ to obtain the molecular sieve precursor. 2) Preparation of the additive metal-modified molecular sieve composite carrier: 470.9 mg of lanthanum nitrate (La(NO3)3·6H2O) was dissolved in 20 mL of deionized water. The molecular sieve precursor obtained in step 1) was added to the solution. The mixture was stirred continuously at room temperature, the pH was adjusted to 11, and the mixture was sealed and stirred for 12 h. The solution was then hydrothermally crystallized at 90 °C for 12 h, filtered, dried, and finally calcined in a muffle furnace at 600 °C for 4 h at a heating rate of 5 °C / min to obtain the Ce-modified molecular sieve composite carrier. 3) Loading of active metal components: At room temperature, 8.5 mg of palladium acetate (Pd(CH3COO)2) was weighed and dissolved in 20 mL of ethanol. 0.4 g of the composite support obtained in step 2) was added, sealed and stirred for 12 h, dried, and calcined in a muffle furnace at 400 °C for 4 h at a heating rate of 5 °C / min to obtain the final catalyst.

[0053] Comparative Example 5 The catalyst used in this comparative example is hydroxyapatite-supported Ni, which does not contain molecular sieves. The specific preparation steps are as follows: 1) Preparation of hydroxyapatite support: At room temperature, 2g of calcium chloride was dissolved in 17mL of deionized water, the pH of the solution was adjusted to 11, and then ammonium hydrogen phosphate ((NH4)2HPO4) solution with pH 11 was added until the Ca / P atomic ratio in the system was 1.67. The mixture was sealed and stirred for 12h, and the solution was hydrothermally crystallized at 90℃ for 12h. The solution was then filtered, dried, and finally calcined in a muffle furnace at 600℃ for 4h at a heating rate of 5℃ / min to obtain the hydroxyapatite support. 2) Loading of active metal components: At room temperature, 34.6 mg of nickel acetate (Ni(CH3COO)2·4H2O) was weighed and dissolved in 20 mL of ethanol. 0.4 g of the hydroxyapatite support obtained in step 1) was added, and the mixture was sealed and stirred for 12 h. After drying, the mixture was calcined in a muffle furnace at 600 °C for 4 h at a heating rate of 5 °C / min to obtain the final catalyst.

[0054] Application examples The catalysts prepared in Examples 1-5 and Comparative Examples 1-5 were used in methane steam reforming for hydrogen production or methane catalytic combustion reactions, respectively, to evaluate the performance of the catalysts. Specifically, for the methane steam reforming for hydrogen production, 40-60 mesh pressed catalyst powder was placed in a continuously flowing fixed-bed quartz tube reactor. The catalyst was reduced in pure hydrogen for 1 hour, after which feed gas was introduced into the reactor at atmospheric pressure with a feed space velocity of 36000 mL / h / g. cat The reaction temperature was 750℃; the feed gas was a mixture of methane / water vapor / nitrogen (methane, water vapor, and nitrogen in a volume ratio of 1:2:2). The catalyst stability test results are shown below. Figure 5 For the catalytic combustion reaction of methane, catalyst powder, compressed into tablets of 40-60 mesh, is placed in a continuously flowing fixed-bed quartz tube reactor. Then, the feed gas is introduced into the reactor at atmospheric pressure with a feed space velocity of 30,000 mL / h / g. cat The catalyst activity was tested at 700℃; the feed gas was a methane / oxygen / nitrogen mixture (methane, oxygen, and nitrogen volume ratio of 1:20:79). The catalyst stability test results are shown below. Figure 6 .

[0055] Figure 1 Characterization diagram of the catalyst prepared in Example 1 before and after catalyzing the steam reforming reaction of methane (reaction time: 12 h). Figure 1 Images (a) to (c) are bright-field TEM images of the catalyst before the reaction, as shown below. Figure 1 As shown in the TEM image in (a), the catalyst exhibits a morphology of regular hexagonal prisms and rod-shaped nanoparticles crosslinked together, displaying a multi-level structure of "heterogeneous splicing." The hexagonal prisms are mainly attributed to the framework structure of the S-1 molecular sieve, indicating that the composite process did not disrupt the macroscopic crystal morphology of S-1. The rod-shaped nanoparticles are mainly HAP (conventionally irregular spherical particles), and their tight crosslinking with S-1 is evident, directly confirming the successful composite of HAP and S-1 molecular sieve. Further observation... Figure 1 Images (b) and (c) clearly show that a large number of small (less than 5 nm) nanoparticles are uniformly attached to the edges and surface of the S-1 bulk particles. These surface-modified particles should be Ni nanocrystals, indicating that Ni grains have good dispersion on the support surface. Meanwhile, some Ni grains with larger sizes were also observed on the surface of the HAP, suggesting that the S-1 molecular sieve in the catalyst can more effectively confine the Ni active component. Furthermore, to clarify the elemental composition and spatial distribution uniformity of the catalyst, elemental surface scan analysis was performed. Figure 1As shown in (d) to (i), the dark field image on the left shows the surface microstructure of the test area, while the corresponding elemental distribution map (EDS Mapping) on ​​the right visually presents the spatial distribution of each element. The elements exhibit a highly overlapping and uniform distribution throughout the scanning area, which not only indicates that the molecular sieve channels are rich in Ca and P, but also further confirms the high dispersion of Ni inside the S-1 molecular sieve. Figure 1 Images (j) to (l) are bright-field TEM images of the catalyst after the reaction, (m) is a dark-field TEM image, and (n) to (r) are EDS mappings of Si, O, Ca, P, and Ni elements, respectively. Comparison with fresh catalysts shows that no significant Ni agglomeration was observed on the surface of the S-1 molecular sieve in the composite material after a prolonged catalytic reforming reaction; only partial Ni sintering agglomeration was observed on the HAP surface outside the S-1 molecular sieve. Based on the above microscopic characterization results, the HAP / S-1 composite material has been successfully synthesized and exhibits excellent structural stability and compositional homogeneity under high-temperature hydrothermal conditions, effectively inhibiting Ni grain growth.

[0056] Figure 2 Characterization diagram of the catalyst prepared in Example 4 before and after catalyzing the steam reforming reaction of methane (reaction time: 12 h). Figure 2 (a) and (b) are SEM images of the catalyst before the reaction. Compared with the traditional SBA-15 molecular sieve, its morphology still shows a blocky shape, but the cross-section of the catalyst block particles becomes rough, which may be due to the HAP coating SBA-15. Figure 2 Image (c) shows the SEM image of the catalyst after the reaction. Obvious accumulation of fine particles can be seen in the cross-section of the bulk particles; these particles are likely primarily composed of HAP. After... Figure 2 Mapping analysis of (d) to (g) shows that Ni and Ce elements are uniformly distributed on the surface of the entire bulk particles, which means that the high-temperature steam reaction conditions did not lead to the agglomeration of Ce and Ni crystals in the catalyst.

[0057] Figure 3 Characterization graphs of the catalyst prepared in Comparative Example 3 before and after catalyzing the steam reforming of methane (reaction time: 12 h). From Figure 3 The SEM images of the catalyst before reaction in (a) and (b) show that the catalyst mainly has a blocky morphology, which is consistent with the morphology of traditional SBA-15. The cross-section of the catalyst block particles is relatively smooth and there is no obvious encapsulation phenomenon. Figure 3 Image (c) shows the SEM image after the reaction, revealing clear particle accumulation at the cross-section of the bulk particles. After... Figure 3Analysis of the EDSMapping diagrams of (d) to (g) shows that Ni is uniformly distributed on the surface of the bulk particles, while Ce is mainly concentrated in the pores of the cross section. Therefore, it can be determined that the particle accumulation here is mainly caused by the sintering of CeO2 grains at the edge of the pores.

[0058] Figure 4 Characterization diagrams of the catalyst prepared in Comparative Example 5 before and after catalyzing the steam reforming of methane (reaction time 12 h) are shown. Figure 4 (a) is a TEM dark field image of the catalyst before the reaction, and (b) is an EDS-Mapping image of the Ni element of the catalyst before the reaction. It can be seen that the active metal Ni grains loaded on the surface of the pure HAP support are mainly distributed at a size of about 12 nm. Figure 4 (c) is a TEM dark-field image of the catalyst after the reaction, and (d) is an EDS mapping image of the Ni element in the catalyst after the reaction. It can be seen that the particle size of Ni grains mainly increases to about 21 nm after the reaction. This result indicates that under high-temperature steam reforming reaction conditions, the Ni active component on the catalyst surface undergoes significant particle growth and sintering, leading to a decrease in metal dispersion.

[0059] Depend on Figure 5 It can be seen that the methane conversion rate of the catalysts prepared in Examples 1, 3, and 4 remained stable within 12 hours during methane steam reforming to hydrogen, without showing a decreasing trend, indicating that the three catalysts have excellent hydrothermal stability. Compared with Example 3, Example 4 only added the auxiliary metal Ce, which significantly improved the activity of the catalyst without affecting its hydrothermal stability. This may be because the introduction of Ce improves Ni dispersion, enhances metal-support interaction, and promotes carbon deposition removal, thereby inhibiting Ni sintering and carbon deposition, and thus improving the activity and stability of the catalyst.

[0060] Compared to Example 1, Comparative Example 1, without HAP modification, showed a rapid decrease in the activity of the catalyst for hydrogen production during the initial stage of the reaction, while the methane conversion rate decreased slowly within 12 hours. This indicates that HAP modification effectively enhances the hydrothermal resistance of the S-1 molecular sieve. Compared to Example 4, Comparative Example 3, without HAP modification, showed a slow decrease in the activity of the catalyst within 12 hours, further illustrating the necessity of HAP modification for improving the hydrothermal resistance of the molecular sieve. Comparative Example 5 was a pure HAP-supported Ni-based catalyst. Combining the activity and stability of the pure S-1 molecular sieve-supported Ni catalyst prepared in Comparative Example 1 and the catalyst prepared in Example 1, it can be seen that the combination of HAP and molecular sieve is necessary to effectively improve the hydrothermal stability of the molecular sieve.

[0061] Depend on Figure 6It can be seen that the methane conversion rate of the catalysts prepared in Examples 2 and 5 remained stable within 24 hours, without a significant downward trend, indicating that the two catalysts have excellent hydrothermal stability. Compared with Example 2, Example 5 only added the auxiliary metal La, which significantly improved the activity of the catalyst without affecting its hydrothermal stability. This may be because the introduction of La improves the dispersibility of Pd, enhances the metal-support interaction, and inhibits Pd sintering, thereby improving the activity and stability of the catalyst.

[0062] Compared to Example 2, Comparative Example 2, without HAP modification, showed a slow decrease in the methane catalytic combustion activity of the prepared catalyst within 24 hours, indicating that HAP modification effectively enhanced the hydrothermal resistance of the S-1 molecular sieve. Compared to Example 5, Comparative Example 4, without HAP modification, showed a rapid decrease in the activity of the prepared catalyst within 24 hours, further illustrating the necessity of HAP modification for improving the hydrothermal resistance of molecular sieves.

[0063] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.

Claims

1. A method for preparing a high hydrothermal stability molecular sieve composite catalyst, characterized in that, Includes the following steps: A template agent and a calcium source are dissolved in water, and the pH value is adjusted according to the choice of template agent. Then, a silicon source is added, and hydrothermal crystallization is performed once. The solid is separated and dried to obtain a Ca-doped molecular sieve precursor. The Ca-doped molecular sieve precursor is dispersed in water, and the pH value is adjusted to 11-12. A phosphate solution with a pH value of 11-12 is added until the Ca / P atomic ratio of the system is 1.60-1.

67. After stirring, a second hydrothermal crystallization is performed, and the solid is separated and dried. Then, it is calcined once to obtain a hydroxyapatite-modified molecular sieve. The hydroxyapatite-modified molecular sieve is mixed with a solution containing an active metal precursor, and stirred so that the hydroxyapatite-modified molecular sieve completely absorbs the solution containing the active metal precursor. Then, it is dried and calcined a second time to obtain the high hydrothermal stability molecular sieve composite catalyst. The active metal in the active metal precursor includes nickel or palladium; The template agent includes Pluronic P123, Pluronic F127, or tetrapropylammonium hydroxide; When the template agent is Pluronic P123 or Pluronic F127, adjust the pH value to 1-2 before adding the silicon source; when the template agent is tetrapropylammonium hydroxide, adjust the pH value to 10-12 before adding the silicon source.

2. The preparation method of the high hydrothermal stability molecular sieve composite catalyst according to claim 1, characterized in that, The molar ratio of Ca in the calcium source to Si in the silicon source is (0.5~2):10; and / or, the active metal in the active metal precursor accounts for 0.5~3% of the mass of the hydroxyapatite-modified molecular sieve.

3. The method for preparing the high hydrothermal stability molecular sieve composite catalyst according to claim 1, characterized in that, The temperature of the primary hydrothermal crystallization is 100~200℃ and the time is 24~72h; and / or the temperature of the secondary hydrothermal crystallization is 80~100℃ and the time is 5~24h.

4. The method for preparing the high hydrothermal stability molecular sieve composite catalyst according to claim 1, characterized in that, The first calcination temperature is 500~600℃, the holding time is 4~8h, and the heating rate is 5~10℃ / min; and / or, the second calcination temperature is 400~600℃, the holding time is 3~6h, and the heating rate is 5~10℃ / min.

5. The method for preparing the high hydrothermal stability molecular sieve composite catalyst according to claim 1, characterized in that, When the template agent and the calcium source are dissolved in water, an auxiliary metal precursor is also added, wherein the auxiliary metal in the auxiliary metal precursor includes cerium or lanthanum.

6. The method for preparing the high hydrothermal stability molecular sieve composite catalyst according to claim 5, characterized in that, The molar ratio of the auxiliary metal in the auxiliary metal precursor to Ca in the calcium source is (0~3):10, and is not 0.

7. A high hydrothermal stability molecular sieve composite catalyst prepared by the preparation method of the high hydrothermal stability molecular sieve composite catalyst according to any one of claims 1 to 6.

8. The application of the high hydrothermal stability molecular sieve composite catalyst of claim 7 in catalytic methane reforming for hydrogen production or catalytic combustion of methane.

Citation Information

Patent Citations

  • Method for preparing nickel-based methane dry reforming catalyst

    CN109647495A

  • Method for solid-phase extraction of rice protein

    CN114748892A